Prospective Trial of Sacroiliac Joint Fusion Using 3D-Printed Triangular Titanium Implants: Five-Year Follow-Up - Patel, Vikas; Meyer, S Craig; Kovalsky, Don; Lockstadt, Harry; Farris, Jim; Limoni, Robert; Chowdhary, Abhineet; Yuan, Philip; Langel, Casey; Kranenburg, Andy; Tender, Gabriel (Spine (Philadelphia, Pa. 1976), 2025)
Prospective, multicenter, single-arm study with five-year follow up. To report long-term (five years) safety, effectiveness, and radiographic outcomes after sacroiliac (SI) joint fusion (SIJF) with 3D-printed triangular titanium implants (TTI) and compare them with solid titanium plasma spray coated implants. A large literature base supports minimally invasive SIJF with TTI for chronic SIJ dysfunction. SIJF with TTI was performed in 51 subjects and scheduled follow-up occurred at 3, 6, 12, 24, and 60 months. Postoperative visits included quality of life questionnaires and functional tests. A high-resolution CT scan was performed at either 6 or 12 months, and again at 60 months. All CT scans were interpreted by an independent musculoskeletal radiologist. Five-year follow-up was available in 36 of 51 subjects (71%). At five years, improvements in SI joint pain [58.1 points (0-100 scale)], SIJ-related disability [Oswestry disability index (ODI), 25.4 points) and quality of life (EuroQOL 5D: 0.24 points and EuroQOL visual analog scale: 13.4 points) were sustained and showed no signs of diminution. The percentage of patients using opioids for SIJ pain decreased markedly from baseline (57%) to five years (17%). Physical function tests showed persistent improvements from baseline. There was no evidence of device breakage, migration or subsidence and few late adverse events occurred attributable to the device. Independent analysis of CT scans showed bone opposed to implants in all cases, and evidence of bone bridging in 90% of cases, and no evidence of radiolucency or other adverse bone reactions. Prospective five-year follow-up showed that SIJ fusion using 3D-printed TTI resulted in immediate, marked, and persistent improvements in pain and quality of life, with improved physical function, reduced opioid use, and a low rate of revision surgery. Radiographic evidence showed implant integration and joint fusion. Level II.